Restoring Ruhiology Quotient in 21st Century Holistic Education - Iskandar, Iskandar (International Journal on Advanced Science, Education, and Religion, 2025)
Technological advances in the Industrial Revolution 4.0 and Society 5.0 eras have facilitated access to information, but have also led to negative impacts such as identity and spiritual crises, known as "westomania." Current national education practices, dominated by the Intellectual Intelligence (IQ), Emotional Intelligence (EQ), and Spiritual Intelligence (SQ) approaches, often fail to shape strong character and noble morals. This study introduces a new paradigm, namely the Ruhiology Quotient (RQ), as a solution to bridge the gap between academic intelligence and spiritual depth. RQ is defined as the ability to present soul energy (God Light), which functions as a source and driver and glue for other intelligences (IQ, EQ, SQ, and Artificial Intelligence/AI). This concept is rooted in the Islamic view of the spirit, which is the core of human existence and the source of all true intelligence. Through a qualitative-descriptive approach, this study examines the urgency of restoring Ruhiology to achieve the goals of national education as a whole. The results show that education centered on RQ will produce a golden generation that is not only intelligent, but also possesses spiritual depth and noble morals, and is able to balance technological advancement with humanitarian values. The implementation of Ruhiology through holistic education offers a model that transintegrates science and technology and faith and piety, thus creating individuals who are adaptive, productive, and virtuous.